Lean body mass, muscle fibre size and muscle function in cancer patients during chemotherapy and 10 weeks exercise. Issue 1 (1st January 2017) - Lønbro, Simon; Farup, Jean; Bentsen, Signe; Voss, Thomas; Rittig, Nikolaj; Wang, Jakob; Ørskov, Morten; Højris, Inger; Mikkelsen, Ulla Ramer
Abstract: Background: Chemotherapy can reduce muscle mass in cancer patients but the potential of exercise to ameliorate this is understudied, particularly at the myocellular level. The primary purpose was to investigate changes in lean body mass (LBM) and secondly single fibre cross‐sectional area (CSA) in cancer patients during chemotherapy and in combination with 10 weeks of exercise. Methods: In a single‐arm trial, patients adhered to chemotherapy for at least 4 weeks (control period) before 10 weeks of exercise adjunct to chemotherapy (exercise period). LBM (Dual Energy X‐ray Absorptiometry) and single fibre CSA (muscle biopsies) were assessed at baseline, pre‐ and post‐exercise. Muscle strength, functional performance and aerobic capacity were also assessed. Results: Ten patients were included, however only six patients completed the protocol. LBM changed over time (p=0.013), but no significant changes were observed between specific time points. Numerically, LBM decreased by 0.3 kg (p=0.41, 95% CI: ‐1.1;0.5) from 41.3–41.0kg, during the control period and increased by 0.7 kg (p=0.16, 95% CI: ‐0.6;2.0) from 40.4–41.1 kg during exercise. Muscle fibre CSA did not change significantly over time (p=0.13), but decreased numerically in the control period by 703 μm 2 (p=0.20, 95% CI: ‐1877; 470) and increased by 846 μm 2 (trend, p=0.08, 95% CI: ‐162; 1854) following exercise. Muscle strength and functional performance were unchanged during the control period but improved post‐exercise. Conclusions: Despite non‐significant changes in muscle mass (due to small sample size), this study adds novel information on LBM and myocellular changes in cancer patients during chemotherapy and concurrent exercise.